BASIC PRINCIPLES, A METHODOLOGICAL APPROACH CORINE LAND COVER IN B&H AND ANALYSIS OF RESULTS CLC2000 AND CLC2006 - Jasmin Taletović; Fahrudin Đuzo; Sead Vojniković; Melisa Ljuša; Hamid Čustović (Geodetski Glasnik, 2012)
Basic principles, methodological approach to the CORINE Land Cover database–revision and correction of the CORINE 2000 (the first inventory) and preparation of the CLC2006 database are shown. The CORINE Land Cover 2006 project in Bosnia and Herzegovina (CLC2000 and CLC2006) is used as a main source of data in this paper. Special attention will be given to the metodological approach in identifying land use changes, land cover between 2000-2006. Bearing in mind that land use changes have been produced by using GIS technology, this work present GIS as a tool, while various possibilities of this tool regarding data analysis presented as well. The possibility of using the CORINE 2006 in land use planning processes in B&H is presented.